Chemical characteristic of Fly ash and Bottom ash as potential source for synthesis of Aluminosilicate-based materials - Elda ALYATIKAH; Siswo; Riaa Safitri; Tety Wahyuningsih Manurung; Rendy Muhamad Iqbal (UNIB Press, 2022)
The world's population has reached 7 billion or doubled from the previous half-century and continues to increase every year. This increase in population is directly proportional to the increase in electrical energy consumption. Electricity needs in Indonesia are mostly met by Steam Power Plants. Unfortunately, the use of coal as an energy source in Steam Power Plants can cause environmental pollution, namely the waste generated by fly ash and bottom ash. However, even though it is classified as hazardous materials, silica (SiO2) and alumina (Al2O3) content in the waste are high enough so that it can be used for the synthesis of aluminosilicate-based materials. The ash waste in this study was obtained from the Steam Power Plant in Kapuas Regency, Central Kalimantan Province which was tested according to the ASTM D93-10 standard. The composition of SiO2, Al2O3, Fe2O3, and CaO in fly ash was 56.44; 31.31; 0.51; 0.78%. The compositions of SiO2, Al2O3, Fe2O3 and CaO in the bottom ash were 66.66; 17.09; 0.31; 5.40%. Based on its composition, fly ash and bottom ash are classified as type F ash. In addition, fly ash and bottom ash have SiO2/Al2O3 ratios of 3.90 and 1.80, respectively. It can be concluded that fly ash and bottom ash has the potential to be used as basic materials for the manufacture of aluminosilicate-based materials such as geopolymers, zeolites, and others.